ENFORCEMENT OF “BACOKAN” CRIME LAW AS A WAY OF CONFLICT RESOLUTION - Galuh Setyowati, Yanna; Wahyudi, Eko (Universitas Islam Balitar, 2024)
Stabbing is a criminal crime committed by someone using a sharp weapon, with the aim of hurting or even killing another person as a means of revenge. Likewise in the Tuban Regency area itself, where the crime of stabbing is normal, because it is considered a hereditary custom carried out to resolve conflicts. Every year, stabbing crimes in Tuban Regency always occur, resulting in fatalities such as injuries and even death, this is because in enforcing the law, stabbing crimes in Tuban Regency experience obstacles in terms of law, law enforcement, means or facilities, society and culture. . The method used is empirical juridical with analytical descriptive methods and uses primary and secondary data sources. The results of the research obtained are that there are obstacles in the implementation of law enforcement for the crime of